2023
DOI: 10.1111/vru.13219
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sonographic and CT findings for the identification of renal nodules in dogs and cats

Abstract: Ultrasonography (US) and computed tomography (CT) are used to diagnose neoplastic and non‐neoplastic focal renal lesions in dogs and cats; however, comparative studies between these two diagnostic tools are lacking. The aim of this retrospective, methods comparison study was to evaluate and compare the performance of US compared to CT in identifying at least one renal nodule in animals with confirmed focal renal lesions. Imaging studies of animals with uni‐ or bilateral renal nodules smaller than 3 cm that und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
(67 reference statements)
1
7
0
2
Order By: Relevance
“…The most common cause of renal metastases is reported to be pulmonary carcinoma, which accounts for 25% of renal metastases in domestic animals [ 19 ]. Although no study has specifically investigated the cause of renal metastasis in cats, several studies have reported that feline pulmonary carcinoma can metastasize to the kidneys, with a prevalence ranging from 1.2 to 15.3% [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The most common cause of renal metastases is reported to be pulmonary carcinoma, which accounts for 25% of renal metastases in domestic animals [ 19 ]. Although no study has specifically investigated the cause of renal metastasis in cats, several studies have reported that feline pulmonary carcinoma can metastasize to the kidneys, with a prevalence ranging from 1.2 to 15.3% [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic lesions in the kidney are often microscopic, involving bilateral renal cortices [ 8 ]. Previous studies revealed that kidneys with metastasis from pulmonary carcinoma exhibited multifocal nodules on the renal capsular surface or within the parenchyma [ 11 , 19 ]. In contrast, our study identified renal nodules in only two out of six kidneys with metastatic pulmonary carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations